2018
DOI: 10.1002/job.2267
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and stable: Dynamics of team action patterns and adaptive outcomes

Abstract: The current study draws on work in the areas of team adaptation, team compilation, and small groups as complex systems to predict and test relationships between time, taskwork team mental models, team action patterns, and team effectiveness. Three-person teams performed 9 scenarios of a firefighting simulation distributed over 3 days with discontinuous task changes introduced in the fourth and seventh scenarios (N = 41 teams; 123 individuals). We applied pattern detection algorithm software to the behavioral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 72 publications
2
53
0
Order By: Relevance
“…Some empirical and theoretical work currently underway moves focus away from the more traditional topic of the fit between the leader's style and the situation to more focus on the ability of leaders and followers to appropriately sense when a switch in leadership behavior is appropriate during dynamic situations, and the ability to switch. For example, research evidence suggests that teams benefit from leadership that is efficiently directive in simple, straightforward situations, but that switches to being inclusively participative in complex situations (Uitdewilligen, Rico, & Waller, ). One important factor in this flexible ability may well be a BTP—both for leaders and for followers.…”
Section: Future Research Opportunitiesmentioning
confidence: 99%
“…Some empirical and theoretical work currently underway moves focus away from the more traditional topic of the fit between the leader's style and the situation to more focus on the ability of leaders and followers to appropriately sense when a switch in leadership behavior is appropriate during dynamic situations, and the ability to switch. For example, research evidence suggests that teams benefit from leadership that is efficiently directive in simple, straightforward situations, but that switches to being inclusively participative in complex situations (Uitdewilligen, Rico, & Waller, ). One important factor in this flexible ability may well be a BTP—both for leaders and for followers.…”
Section: Future Research Opportunitiesmentioning
confidence: 99%
“…It offers an optimal data collection environment for the testing of new theory because experimenters have more control and data accessibility than in naturalistic settings (Marlow et al, 2017). In addition, the adoption of simulations has been proven highly effective in I/O Psychology and Human Factors research, and the number of empirical studies showing that simulations are most beneficial for research and training is growing (e.g., Uitdewilligen et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Occasionally, either driven by internal or external triggers, the relative stability that exists in self-organized states is disrupted. Such discontinuities in team functioning are well documented in the work of authors such as Gersick’s (1991) punctuated equilibrium model, or Uitdewilligen et al (2018), who found that team processes and team performance unfold over time through longer periods of stability, which alternate with shorter periods of instability where discontinuities occur.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several articles in this special issue focus on temporal patterns and emergence. First, Uitdewilligen, Rico, and Waller () used pattern detection algorithms to identify action patterns (i.e., recurrent sequences of actions) when team members collaborate on an assignment. They then examined how these action patterns dynamically emerged over time and how are they related to overall team effectiveness.…”
Section: The Time Has Come To Study Dynamics At Workmentioning
confidence: 99%